An examination of possible relationships between paleoenvironmental conditions during the PleistoceneeHolocene transition and human occupation of southern Patagonia (Argentina) east of the Andes, between 46º and 52º S - Brook, George (2013)
Spatial and temporal variations in evidence for human occupation of Argentinian south Patagonia closely resemble changes in past vegetation reconstructed from pollen records. The Antarctic Cold Reversal was cold and dry in the Deseado Massif and there is little evidence of humans at this time. In contrast, the Younger Dryas interval was warmer and slightly wetter and this was when humans moved into the Deseado area. Increasing temperatures during the early Holocene brought higher precipitation to much of Patagonia east of the Andes except the northern Deseado Massif, explaining the increase in evidence of human occupation in western areas and the decrease in evidence in the massif. Spatial and temporal variations in the frequency of radiocarbon dates indicating human presence, show that in southern Patagonia humans were not only influenced by the major climate shifts of the Pleistocene-Holocene transition but possibly also by distinct short-term changes lasting only a few to several centuries that are apparent in the high-resolution Antarctic Byrd ice core. Water availability may have had the greatest influence on human use of the landscape rather than temperature. However, as temperature is crucial in controlling the latitude of the core of the Southern Westerly Winds, associated with reduced precipitation over most of eastern Patagonia, it is difficult to separate water from temperature in examining impacts on the first humans in southernmost South America.